Death Trends and Years of Life Lost Due to Social Harms Such as Suicide, Homicide, and Addiction, Ilam Province, 2009-2019 - Zahra Jalilian; Fathola Mohamadian; Yousef Veisani; Sasan Ahmadi (Bulletin of Emergency and Trauma, 2023)
Objective: This study aimed to investigate the death trend and years of life lost (YLL) caused by social harmin Ilam province.Methods: This cross-sectional study was conducted in Ilam province from 2009 to 2019. To estimate YLL, alldeaths caused by suicide, homicide, and addiction were included in the study. The data were collected from theForensic Medicine Organization. The analysis was carried out using SPSS software (version 23.0). A p-valueof <0.05 was considered statistically significant.Results: Between 2009 and 2019, there were 1712 occurrences of suicide, homicide, and addiction, whichresulted in a total of 62,605 years of lost life (53,934 per 100,000 people). The highest frequency was relatedto the age group of 15-29 years, while the lowest was related to the age group of 0-14 years (p<0.001). Duringthe studied period, men were more likely than women to commit suicide, homicide, and addiction in Ilam(p>0.439). Between 2009 and 2019, the number of suicides and homicides in Ilam province started a decreasingtrend for both sexes, while the number of deaths caused by addiction was increasing.Conclusion: The results of this study indicated that the age groups of 15-29 years had the highest rate ofYLL is caused by suicide, homicide, and addiction for both sexes. Furthermore, the findings showed that YLLdecreased for suicide and homicide, but increased for addiction.